Da'wah Strategy in Dealing with Hoax News on Social Media (Critical Review of Opinions of Da'wah Faculty Students of IAI Al-Azis Batch VIII) - Aldina Mutiara; Alfi Satria; Ahmad Asrof Fitri (International Forum of Researchers and Lecturers, 2024)
Social media is the main source of information. However, it can also serve as a platform for spreading hoaxes that threaten digital literacy in society. Therefore, an effective da'wah strategy is needed to counter hoaxes, especially among students of the Faculty of Da'wah at IAI Al-Zaytun Indonesia. Students play a key role in understanding and spreading the values of truth and increasing digital literacy in society. This study aims to explore what actions are being taken and the da'wah strategies employed by the students of the Faculty of Da'wah, IAI AL-AZIS, Class VIII. The research method is qualitative, using a case study approach. The data collected for this study came from observations and interviews with students of the Faculty of Da'wah, IAI AL-AZIS, Class VIII. The study results indicate that students of the Faculty of Da'wah, IAI AL-AZIS, Class VIII, have a crucial role in tackling the spread of hoaxes on social media. They adopt several strategies, such as verifying information (tabayyun), ignoring dubious news, reporting accounts spreading hoaxes, and engaging in healthy debates to provide clarification. Most students don't pay much attention to hoaxes, but a small portion are actively involved in countering their spread. This highlights that students from the Faculty of Da'wah are both proactive and responsive in ensuring the accuracy of information and reducing the harmful effects of hoaxes.